Islamic Religious Education Teachers' Strategies in Increasing Religious Awareness - Istiqomah Rahmasari; Chusniatun, Chusniatun (Tadrib: Jurnal Pendidikan Agama Islam, 2026)
Religious awareness is very important for students to give direction to a righteous life physically and spiritually. The strategy of Islamic Religious Education teachers plays a role in fostering religious awareness in students so as to form a person with noble character. The research uses a type of qualitative research with a descriptive approach through interviews, observations and documentation and the source of research data is Islamic Religious Education teachers and students of SMK Muhammadiyah 3 Karanganyar. The results of the study show that Islamic Religious Education teachers in increasing religious awareness at SMK Muhammadiyah 3 Karanganyar use several strategies including through the habit of congregational prayer, giving advice through general studies, motivation, and theoretical knowledge applied since 2015 for all students from grades 10, 11 and 12. With the implementation of this strategy, it is hoped that all students will be accustomed to doing worship such as prayer so as to form a person with noble and disciplined character and responsibility. In addition to building character, this strategy aims to give students an understanding that every kindness has a positive impact on themselves and others.